Theo bất đẳng thức Cô-sy ta được:
\(a+b+c\ge3^3\sqrt{abc}\)(1)
\(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\ge3^3\sqrt{\frac{1}{abc}}\)(2)
Nhân (1) (2) vế heo vế ta được
\(\left(a+b+c\right)\left(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\right)\ge9\)
\(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\ge\frac{9}{a+b+c}=\frac{9}{1}=9\)
biến đổi cách này dễ hiểu hơn nề:))
vì a+b+c=1 nên
\(\frac{1}{a}\)=\(\frac{a+b+c}{a}\)= 1+ \(\frac{b}{a}\)+\(\frac{c}{a}\)
\(\frac{1}{b}\)=\(\frac{a+b+c}{b}\)= 1+ \(\frac{a}{b}\)+\(\frac{c}{b}\)
\(\frac{1}{c}\)=\(\frac{a+b+c}{c}\)= 1+ \(\frac{a}{c}\)+\(\frac{b}{c}\)
ta có \(\frac{1}{a}\)+\(\frac{1}{b}\)+\(\frac{1}{c}\)= 1+1+1+(\(\frac{a}{b}\)+\(\frac{b}{a}\))+(\(\frac{a}{c}\)+\(\frac{c}{a}\))+(\(\frac{b}{c}\)+\(\frac{c}{b}\))
ta lại có \(\frac{a}{b}\)+\(\frac{b}{a}\)\(\ge\)2 \(\Leftrightarrow\)\(\frac{a^2+b^2}{ab}\)\(\ge\)2\(\Leftrightarrow\)\(a^2\)+\(b^2\)\(\ge\)2ab \(\Leftrightarrow\)(a-b)^2\(\ge\)0 luôn đúng
tương tự ta có a/c+c/a >= 2 và b/c+c/b >= 2
vậy 1/a+1/b+1/c>=9